Comparison of biochemical indicators of prooxidant status and antioxidant system in patients with COVID-19 with accompanying cardiovascular pathology - Titova, I. S.; Guitur, M. M.; Shvets, V. M.; Гуйтур, Михайло Михайлович; Швець, Володимир Миколайович (Харків : НФаУ, 2023)
Special attention is drawn to the problem of the state of free radical processes in patients with COVID-19, who suffer from a complex of cardiovascular diseases, which is an extremely frequent phenomenon. According to the WHO, in recent years there has been a significant increase in the incidence of coronary heart disease, arterial hypertension, and heart failure.
Keywords: COVID-19; oxidative stress; diene conjugates; malondialdehyde; catalase; tocopherol; antioxidants